Ninety-two poems and hymns of Yehuda Halevi - Judah, ha-Levi, active 12th century (Book collections on Project MUSE., 2000)
"This is the first publication in English of Franz Rosenzweig's 1927 translation of and commentaries on ninety-two poems and hymns of the greatest medieval "singer of Zion," Yehuda Halevi (born circa 1080). Franz Rosenzweig (1886-1929) is widely recognized as one of the greatest Jewish philosophers of the modern period and his Star of Redemption is considered one of the most important twentieth-century contributions to Jewish - and Christian - theology."--Jacket